Clinical use of amino acids as dietary supplement: pros and cons - Francesco S. Dioguardi (2011)
Nitrogen supply is pivotal for the maintenance of life. Amino acids can be utilized to synthesize both glucose and lipids. The opposite, i.e., production of amino acids from either one of them, is not possible in the absence of other amino acids as donors of nitrogen. The quality of amino acid content in protein has been re-evaluated recently, and the relevance of essential amino acids has been repeatedly underlined. Essential amino acid requirements in different mammals are not identical, and ratios among them should be taken into account when projecting an efficient formulation. Recent research has demonstrated that genes respond to different qualities and quantities of nutritional supply, and increased provision of essential amino acids increases lifespan in animal experiments through mitochondriogenesis and maintenance of elevated rates of synthesis of anti-oxidant molecules. Moreover, genetic expression of key controllers of synthesis, like mTOR, may be particularly important for understanding skeletal muscle maintenance. Losses of muscle mass and impaired immune function are related to reduced protein supply, and there is increasing evidence that regular essential amino acid intake as part of an oral diet is effective in reversing muscle catabolism, promoting muscle anabolism, and restoring immunological function. Therefore, the use of amino acids as supplements to diet would be expanding in the near future. Is this safe? Few data are available on amino acid toxicity, and only one essential amino acid may be considered to have clinically relevant toxicity: methionine, because it is transformed into a toxic intermediate, homocysteine, when cysteine synthesis is required by metabolic needs. Matching of stoichiometric ratios between methionine and cysteine may solve the problem of supplying sufficient amounts of sulfur to the body. Arginine and glutamine are two non-essential amino acids than can become "conditionally essential" because of elevated needs during pathological conditions, and metabolism may not be able to maintain their concentrations at sufficient levels to match metabolic requirements. Chronic exogenous arginine supplementation has not proven to exert positive clinical effects in different trials, and sequential articulation of the knowledge of introduction of arginine-driven transcriptional, translational, and epigenetic adaptations may give us a key for interpreting those puzzling results.